SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK PEMILIHAN MEKANIK TERBAIK PADA PT GEMILANG BERLIAN INDAH - Herrianto Herrianto; Sulistianto Sutrisno Wanda (Jurnal Informatika Kaputama (JIK), 2023)
This study aims to analyze the application of a decision support system on the selection of the best mechanics at PT. Brilliant Beautiful Diamonds. In the assessment process for the selection of the best mechanic, there is no definite system in the assessment so that the process is not optimal and takes a long time. To overcome this problem, it is necessary to renew the existing mechanical selection system, one of the steps taken is to implement a decision support system. The analytical method used in this study is the Simple Additive Weighting (SAW) method which is a weighted summation method of performance ratings on each alternative on all attributes. There are several criteria taken from the selection of the best mechanics, namely Standard Operating Procedure (SOP), performance, responsibility, discipline, cooperation, and skills. The results of this study can be concluded that this system can be used as an auxiliary application for the best mechanical recommendations quickly and efficiently.